2011
DOI: 10.3109/08916934.2011.622013
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms inTBX21andHLXare associated with development and prognosis of Graves' disease

Abstract: Functional polymorphisms in TBX21 are associated with the development of autoimmune thyroid diseases and prognosis of GD, and a functional polymorphism in HLX in combination with the TBX21 polymorphism is also associated with the prognosis of GD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…We previously reported that Th17 cells and inflammatory cytokines, such as IL-1β, that induce Th17 differentiation were associated with the intractability of GD [8,39,40]. We also reported that lower genetic expression of TBX21, which promotes the differentiation of Th1, was associated with the intractability of GD [11], probably because IFN-γ, a Th1 cytokine, potently inhibits the development of Th17 cells [41]. Therefore, we suggest that higher production of IL-18 may attenuate the intractability of GD through the enhancement of IFN-γ production.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We previously reported that Th17 cells and inflammatory cytokines, such as IL-1β, that induce Th17 differentiation were associated with the intractability of GD [8,39,40]. We also reported that lower genetic expression of TBX21, which promotes the differentiation of Th1, was associated with the intractability of GD [11], probably because IFN-γ, a Th1 cytokine, potently inhibits the development of Th17 cells [41]. Therefore, we suggest that higher production of IL-18 may attenuate the intractability of GD through the enhancement of IFN-γ production.…”
Section: Discussionmentioning
confidence: 95%
“…We previously reported that CD8 + CD25 + activated cytotoxic T cells and Th1 cells were increased in patients with severe HD [8,9] and that higher production of IFN-γ was more frequent in patients with severe HD than in those with mild HD [10]. Moreover, lower expression of T-box 21 (TBX21), the master transcription factor of Th1 cells, was associated with intractability of GD [11]. These data suggest that genetic differences in immune mediating factors that regulate Th1 cells may be associated with the prognosis of AITD.…”
mentioning
confidence: 99%
“…In this aspect our result are in accordance with published evidence. 25,26 However, it is important to notice that despite the strong influence of T allele/genotypes over T-bet expression ( 2 fold), the subsequent impact over IFN-g expression was significantly lower (1.21-fold), and proved statistically non-significant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with theoretical resistance or susceptibility to apical periodontitis development present distinct frequencies of TBX21‐1993 genotypes/alleles, being the polymorphic C allele, and TC and TC+CC genotypes, associated with decreased risk to develop periapical lesions. Interestingly, previous case‐control studies demonstrate that TBX21‐1993T/C influence the risk at different conditions, such as hepatitis, lupus erythematosus, and asthma …”
Section: Discussionmentioning
confidence: 99%